Modulation of the immune microenvironment using nanomaterials: a new strategy for tumor immunotherapy - Piao, Haozhe; Jiang, Yuxin; Jin, Shengbo; Shi, Jie; Yu, Jun; Wang, Wenping; Du, Zhenguang; Yao, Huini; Liu, Qian; Li, Ningxin; Fu, Jiaqing; Shen, Yue; et al. (Frontiers in Immunology, 2025)
The complexity of the tumor immune microenvironment (TIME), which is composed of mainly tumor cells, immune cells, and cytokines, is a major obstacle limiting the effectiveness of immunotherapy, and the interactions among these factors in the TIME determine the efficacy of antitumor immunity. Over the past few years, nanomaterials, owing to their unique physicochemical properties, multifunctionality, and good targeting ability, have gradually become important tools for modulating the immune microenvironment. By precisely delivering immunomodulatory factors, nanomaterials can effectively activate dendritic cells (DCs), enhance the function of effector T cells, and reverse the immunosuppressive state of tumor-associated macrophages (TAMs). In addition, nanomaterials can alleviate the local hypoxic and acidic tumor microenvironment, which in turn promotes immune cell function and enhances the antitumor immune effect. In light of the aforementioned associations, we summarize the existing studies, systematically describe the latest research progress on the use of nanomaterials in regulating the tumor immune microenvironment, and analyze the potential applications and challenges in tumor immunotherapy, with the goal of providing new therapeutic directions and strategies for tumor immunotherapy.